Physiological and genetic characterization of sorghum exposed to early season chilling and terminal heat and drought stress - Chiluwal, Anuj (Kansas State University, 2018)
Sorghum (Sorghum bicolor (L.) Moench) is one of the hardiest crop to abiotic stresses compared with other grain crops. However early stage chilling, terminal heat and drought stress are three most damaging abiotic stresses that have limited sorghum productivity in the US Great plains and other locations having similar environmental conditions. Three studies were conducted with an overall goal aimed at increasing grain sorghum’s resilience to harsh climatic conditions. In the first study, four promising chilling stress tolerant sorghum advanced breeding lines, a known early stage chilling tolerant Chinese landrace (Shan Qui Red - SQR) and a susceptible US elite cultivar (RTx430) as checks were assessed for chilling tolerance during emergence and early growth under field and controlled environments. Aerial phenotyping using unmanned aircraft systems (UAS) fitted with multispectral camera was used to capture reflectance-based vegetation indices (NDVI and NDRE) in field experiments. Some advanced breeding lines with superior agronomic background also recorded significantly better emergence, seedling growth and vigor compared to SQR under chilling conditions. Aerial phenotyping indices from images taken between 30 and 60 days after emergence were consistently correlated with destructive measurements under early plantings, indicating their effectiveness in differentiating chilling responses. Second study was conducted to understand physiological mechanisms inducing heat stress resilience in sorghum during flowering. A diverse set of sorghum inbreds and selected hybrids were tested under greenhouse, growth chamber facilities and field conditions. A highly conserved early-morning-flowering mechanism was observed across all the inbreds and hybrids, with the peak anthesis wherein >90% of florets completed flowering within 30 min after dawn. The conserved response was consistent even under drought stress and heat stress exposure imposed at different times of the day. Our findings report a novel heat escaping early-morning-flowering mechanism effectively employed by sorghum to minimize heat stress impact at anthesis. Another experiment with sequential increase in daytime temperature treatments suggest heat stress induced loss in pollen viability to be a key factor resulting in reduced seed-set and grain yield. The findings suggest heat stress could have a greater impact on post-pollen germination processes such as fertilization, embryo formation and development. We identified a heat tolerant genotype “Macia” which appears to be a promising donor for developing improved heat tolerant sorghum hybrids. In the third study, a bi-parental recombinant inbred lines (RILs) mapping population developed from elite post flowering drought susceptible cultivar (RTx430) and a known drought tolerant cultivar (SC35) were evaluated under wide spectrum of environments and moisture conditions. Several novel and major QTL for grain yield, panicle neck diameter, effective quantum yield of photosystem II and chlorophyll content were identified. The genomic regions and the candidate genes within these regions can potentially help in improving source and sink dynamics in sorghum under diverse environments. The findings from these studies will complement ongoing efforts in developing future sorghum with enhanced resilience to different abiotic stresses that continue to limit sorghum productivity.
Keywords: Sorghum; Abiotic stress; Early stage chilling tolerance; Terminal heat and drought tolerance; Source and sink dynamics; Quantitative trait loci